The Urgence of Whistleblower Legal Protection in the Criminal Justice System - Abdul Wahid (Universitas Lampung, 2022)
The role of the whistleblower is significant in uncovering a case because many cases are not revealed. After all, no one reports or becomes a whistleblower. A whistleblower is legally protected and cannot be prosecuted civilly or criminally. Although currently, there is a Witness and Victim Protection Agency that carries out the task of protecting witnesses and victims, the Witness and Victim Protection Agency have not yet reached out to whistleblowers. The protection is given to whistleblowers only reduces punishment if the whistleblower is involved in the reported case or witnesses the perpetrator. The form of protection given to whistleblowers is legal and unique, and protection is not provided if the witness does not give testimony in good faith. So it is necessary to revise the Criminal Procedure Code and the Law on the Protection of Witnesses and Victims so that the whistleblower who is a witness to the perpetrator is included as one who should be protected by both criminal charges, even though he is the perpetrator and not only reduces the sentence.